PENGARUH INOKULASI JAMUR MIKORIZA ARBUSKULAR PADA PADI TERHADAP PERTUMBUHAN & PERKEMBANGAN WERENG COKLAT (Nilaparvata lugens) - , Hayu Siwi Pribadi, SP, Dr. Ir. Nugroho Susetya Putra, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The aim of this Research is to determine the effect of mycorrhizal fungi on rice Arbuskular to the attack, population and life cycle of brown planthopper (Nilaparvata lugens). This research was conducted in the Green House and Laboratory of Basic Entomology Department of Plant Pest and Diseases Gadjah Mada University from July until October 2011. The experiments will be evaluated using 3 x 2 factorial experiment. Four replicates were included per treatment. The first factor is the provision without mycorrhizal fungi arbuskular. The second factor is the provision of available and unavailable P fertilizer. The third factor is TN1 and IR64. The results show that administration of mycorrhizal fungi Arbuskular: (1) improves the performance of N. lugens, and (2) increases the resistance ofrice IR64.